Contemporary Interpretation Approach In The Culture Of Patriarchal Analysis In Surah An-Nisa Verse 34: Literature Review - Fatimah Salma Az-Zahra; Ahmad Nurrohim (Eduvest - Journal of Universal Studies, 2024)
This study examines the role of Qur'anic interpretation in promoting social welfare, focusing on the implementation of justice values in holy verses, especially in Surah An-Nisa verse 34. The method used is a literature study, which includes an in-depth analysis of various sources of literature related to gender and interpretation. The results show that traditional understandings of gender, which are often rooted in patriarchal societies, result in hierarchies that are detrimental to women. However, contemporary interpretations of this verse seek to challenge this view, offering a more inclusive perspective and emphasizing gender equality. This study concludes that a fairer interpretation approach can contribute positively to gender relations in Muslim society. These findings are expected to enrich academic discussions about gender in Islam and encourage the application of social justice principles in society